2019
DOI: 10.11609/jott.4648.11.12.14511-14517
|View full text |Cite
|
Sign up to set email alerts
|

The distributional pattern of benthic macroinvertebrates in a spring-fed foothill tributary of the Ganga River, western Himalaya, India

Abstract: Benthic macroinvertebrates play important ecosystem roles in the cycling and outflow of nutrients.  The benthos transforms organic detritus from sedimentary storage into dissolved nutrients that can be mixed into overlying waters and used by rooted plants (macrophytes) and algae (phytoplankton) to enhance primary productivity.  This study examined the distribution pattern of benthic macroinvertebrates in a lesser Himalayan foothill stream from the headwaters (2,200m) to mouth (375m).  Five stations (S1 to S5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Consequently, food availability for macroinvertebrates was scarce during this period, compounded by the submergence of the littoral zone. The dominancy of insects (larvae and nymphs) as benthic fauna in the aquatic water bodies in winters has been documented in river Jhelum (Kashmir) 45 , Tons River 46 , and Hinyul stream, a tributary of river Ganga 47 . In this work, 13 genera belonging to 6 orders of macroinvertebrates were collected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, food availability for macroinvertebrates was scarce during this period, compounded by the submergence of the littoral zone. The dominancy of insects (larvae and nymphs) as benthic fauna in the aquatic water bodies in winters has been documented in river Jhelum (Kashmir) 45 , Tons River 46 , and Hinyul stream, a tributary of river Ganga 47 . In this work, 13 genera belonging to 6 orders of macroinvertebrates were collected.…”
Section: Discussionmentioning
confidence: 99%
“…4 ) between three different sites showed that S2 and S3 were similar, whereas S1 was outgroup. Negi and Mamgain 47 also applied cluster analysis for macrozoobenthos to identify homogeneous groups between different months 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Dipteran and Coleopteran species have also been observed in abundance in various streams of Brazil and Solan (HP, India). Many studies were carried out to find out the connection between the benthic communities and abiotic factors as a crucial parameter for the determination of stream degradation levels (Dutertre et al, 2013;Erman & Erman, 1984;Maul et al, 2004;Semwal & Mishra, 2019). Earth's geology directly impacts various physical and chemical features of the aquatic environment (Glazier & Gooch, 1987).…”
Section: Distribution Of Macroinvertebrates In Relation To Geographic...mentioning
confidence: 99%
“…The study of structural composition of benthic macroinvertebrate fauna is governed with various physico-chemical factors such as water quality, sediments quality and biological factors i.e., competition and predation. In view of above global studies, various Indian studies have been conducted in the rivers and streams of different geographical regions like Himalaya (Nautiyal et al 2015, Semwal and Mishra 2019, Mishra and Prasad 2020, the central Highlands , Mishra and Nautiyal 2016 and in the Western Ghat (Dinakaran and Anbalagan 2010, Though many studies have been Santosh et al 2014). performed in the lesser Himalayan region, but very sparse study is available in the rivers of north east Himalaya and especially in the rivers proposed for hydroelectric project.…”
mentioning
confidence: 99%